(untitled) (Baghdad Science Journal, 2019)
Simple, cheap, sensitive, and accurate kinetic- spectrophotometric method has been developed for the determination of naringenin in pure and supplements formulations. The method is based on the formation of Prussian blue. The product dye exhibits a maximum absorbance at 707 nm. The calibration graph of naringenin was linear over the range 0.3 to 10 µg ml-1 for the fixed time method (at 15 min) with a correlation coefficient (r) and percentage linearity (r2%) were of 0.9995 and 99.90 %, respectively, while the limit of detection LOD was 0.041 µg ml-1. The method was successfully applied for the determination of naringenin in supplements with satisfactory results.